Pelas mãos de Comissários do Santo Ofício na Bahia setecentista: edição semidiplomática e estudo do artigo definido diante de pronome possessivo pré-nominal - Brito, Rosana Carvalho (2024)
The objective of this thesis is to contribute to the agenda of constituting diachronic corpora for the study of the history of Brazilian Portuguese, through careful work of a paleographicphilological nature, and to study the patterns of realization/omission of the definite article in the possessive phrase, in Brazilian texts from the 18th century. The research is carried out in the field located in the field of Historical Linguistics covering the areas of constituting diachronic corpora – with the realization of the semi-diplomatic edition of 93 manuscripts produced between 1700 and 1791, by 11 Commissioners of the Holy Office, who were born and worked in Bahia –, of linguistic social history, situating the sample constituted in the dynamics of socio-historical formation of the varieties of Brazilian Portuguese (BP), and of linguistic analysis, with the investigation of the variation presence/absence of the definite article before the pre-nominal possessive pronoun. The edition developed here is of a conservative type, it was based on the second version of the manuscript transcription standards developed by the Projeto Para História do Português Brasileiro (PHPB) team and the editing standards used by the Memória & Arte team (Lose, 2019) and its main objective is to contribute to new data and study of the history of eighteenth-century colonial Brazilian Portuguese. The sociobiographical identification of the scriptores – white, literate men who acquired The Portuguese language through the processes of regular linguistic transmission (Lucchesi; Baxter, 2009), having as available input for acquisition data closer to the European varieties of Portuguese – allows us to locate the sample constituted in the aspect of the prestigious standards of BP. It is assumed, based on the discussion proposed by Mattos and Silva (2004), that the linguistic variety reflected in the edited documents suggests the initial contours of what the author calls cultured Brazilian Portuguese, which in her proposal begins to define itself in the second half from the 18th century. However, instead of the current expression cultured variety, the option in this thesis is to use the expression variety of literate white clergymen from 18th century Bahia, in reference to the variety of Portuguese, which is presented in the edited texts. The Linguistic analysis is descriptive in nature, follows the assumptions of Socio-Historical Linguistics (Mattos and Silva, 2008) and uses quantitative methods for data processing. In this investigation, special attention is given to the semantic conditioning of the uses of the article in relation to possessive pronouns in the data examined. The results show that the realization of the definite article in the possessive phrase is related, among other aspects, to the definiteness of the possessor. It is assumed that the semantic notion of definiteness is best understood in terms of the salience of discursive referents (von Heusinger, 2013). And to measure salience in texts, the analytical instrument of Centering Theory is adopted (Walker; Iida; Cote, 1994; Grosz; Joshi; Weinstein, 1995).